Emerging Scriptures - Schofield, Rodney (Oxford MZUNI Press, 2014)
Cover -- Copyright page -- Title page -- Contents -- Introduction -- 1. Many Roads, One Goal -- PART 1 - Reflecting on the Hebrew Scriptures -- 2. The Jewish Inheritance of Jesus and the Early Church -- 3. Valuing the Hebrew Scriptures -- 4. Israel's History -- 5. Theological Perspectives of the Hebrew Bible -- 6. Messianic Expectations -- PART 2 - Assessing the Christian Writings -- 7. The Earliest Christian Witnesses -- 8. From Oral Testimony to Written Records -- 9. The Emergence of Christian Scripture -- 10. Ongoing Formation of Faith -- PART 3 - Responding to the Qur'an -- 11. Encountering the Qur'an -- 12. The People of the Book -- 13. The Seal of the Prophets -- 14. Some Qur'anic Themes -- 15. Early Christian Responses -- EPILOGUE -- 16. Dialogue Today -- Back cover.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books